A review on molecular breeding technology towards rice sustainability / Nur Azrina Md Yusuf - Md Yusuf, Nur Azrina (Faculty of Plantation and Agrotechnology, 2018)
Molecular breeding technology is widely used nowadays. It is becoming one of big contributor to agriculture especially rice. A sustainable development is a new trend as the population of the world rise higher day by day resulting high demand of food like rice. There are many techniques of molecular breeding applied in agriculture that helps in achieving rice sustainability. Many varieties of paddy have been created such as heat tolerant, herbicide tolerant and more. These varieties are created to make the source of rice sustainable and making rice crop suitable with the climate of one’s place rice crop is planted. In order to achieve sustainable rice supply, molecular breeding is a big part of it and there are some challenges in making it a success.